Neurological Physical Therapy - Suzuki, Toshiaki (IntechOpen, 2017)
Physical therapy services may be provided alongside or in conjunction with other medical services. They are performed by physical therapists (known as physiotherapists in many countries) with the help of other medical professionals. This book consists of 12 chapters written by several professionals from different parts of the world. The book covers different subjects, such as the effects of physical therapy, motor imagery, neuroscience-based rehabilitation for neurological patients, and applications of robotics for stroke and cerebral palsy. We hope that this book will open up new directions for physical therapists in the field of neurological physical therapy.